Quantitative data analysis in communication research - Ahlam Abdul Aziz; Zaridah Abdullah; Antashah Mohd Nor (UiTM Press, 2021)
Quantitative data analysis is a scientific approach that allows researchers to learn a situation or phenomenon through numerical data. It helps researcher to apply the proper methods in collecting data, employing accurate analyses, interpreting the data correctly and effectively presenting the results. Quantitative data helps researcher to discover new knowledge and it helps them in decision making process. This textbook is written especially for Mass Communication and Media Studies students and social science researchers as a step-by-step guidance to analyse quantitative data. This book contains four (4) chapters. Each chapter is carefully explained the appropriate analysis step-by-step by manual calculation and SPSS software through relevant examples so that students can learn both methods of data analyses. Examples with computer output provide opportunities for students to understand and interpret the results of the SPSS output. This books also includes the exercise questions to test the students understanding upon completion of every chapter.